Impact of commercial farming on household reproductive strategies in Calakmul, Campeche, Mexico. Issue 6 (22nd June 2015) - Gurri, Francisco D.; Ortega‐Muñoz, Allan; Gurri, Francisco D.; Ortega‐Muñoz, Allan
<x xml:space="preserve">Abstract</x> Objectives The purpose of this study was to determine if commercial agriculture can lead to changes in peasant reproductive strategies in migrant agriculturalists from Calakmul, Campeche, Mexico. Methods The reproductive histories of 746 women from Calakmul, Campeche, Mexico were collected. The sample was first divided into women who had reproduced within or outside of Calakmul (RC and RO, respectively) and these were further subdivided into those who lived in households practicing subsistence agriculture and those who turned agriculture into a business (Household Subsistence Agricultural Strategy (HSA) and Household Commercial Agricultural Strategy (HCA), respectively). Age‐specific fertility rate (ASFR) differences were compared between strategies and place of reproduction. Comparisons between interbirth interval and age at which desired fertility was reached were done with a Kaplan–Meier life table‐based statistic. Results In both strategies, RC women increased ASFRs by reducing age at first birth, and HSA‐RC women also reduced interbirth intervals. HCA women had lower ASFRs than HSA women. The latter had a natural fertility pattern while the former expressed a desire to stop reproducing at a younger age. HCA‐RC women showed important fertility reductions after age 25 and HCA‐RO women after age 30. Conclusions Fertility reductions in households that practice commercial versus those that practice subsistence agriculture were significant. Also, a "frontier" effect was observed that increased fertility over all, but HCA households were not as influenced by it. Am. J. Hum. Biol. 27:758–766, 2015. © 2015 Wiley Periodicals, Inc.